Arterial counterpulsation in continuing myocardial ischaemia after acute myocardial infarction. - Sammel, N L (1979)
Twenty-six patients underwent arterial counterpulsation for refractory heart failure without shock complicating acute myocardial infarction. Patients were divided into a group of 12 with continuing myocardial ischaemia, evidenced by anginal pain associated with abnormal ST segment elevation, and a group of 14 without continuing ischaemia. Clinical features (apart from pain) and prognostic indices were similar in the two groups when counterpulsation was started but short- and long-term results were different. Hospital survival was 92 per cent (11/12) and 43 per cent (6/14), respectively, in the groups with and without ischaemia and four-year survival was 73 per cent and 7 per cent. Counterpulsation is of greatest value in acute infarction when used to relieve myocardial ischaemia.